Ultra-compact MXene fibers by continuous and controllable synergy of interfacial interactions and thermal drawing-induced stresses - Zhou, Tianzhu (2022)
Recent advances in MXene (Ti3C2Tx) fibers, prepared from electrically conductive and mechanically strong MXene nanosheets, address the increasing demand of emerging yet promising electrode materials for the development of textile-based devices and beyond. However, to reveal the full potential of MXene fibers, reaching a balance between electrical conductivity and mechanical property is still the fundamental challenge, mainly due to the difficulties to further compact the loose MXene nanosheets. In this work, we demonstrate a continuous and controllable route to fabricate ultra-compact MXene fibers with an in-situ generated protective layer via the synergy of interfacial interactions and thermal drawing-induced stresses. The resulting ultra-compact MXene fibers with high orientation and low porosity exhibit not only excellent tensile strength and ultra-high toughness, but also high electrical conductivity. Then, we construct meter-scale MXene textiles using these ultra-compact fibers to achieve high-performance electromagnetic interference shielding and personal thermal management, accompanied by the high mechanical durability and stability even after multiple washing cycles. The demonstrated generic strategy can be applied to a broad range of nanostructured materials to construct functional fibers for large-scale applications in both space and daily lives.